Eksistensi Musholla dalam Pembentukan Nilai Religius pada Akhlaq Anak - Suyanto; Benny Prasetiya; Heri Rifhan Halili (Moderasi : Journal of Islamic Studies, 2022)
The research is intended to identify the bond between the two independent elasticity of the existence of musholla as its x1, and the formation of its religious value as its x2, to the one variable of child morality. The study USES a descriptive quantitative methodology to which the results are derived from those Shared by the respondents through gogle form using Numbers. The object of this study is the santri of the three musholla in the village of krajan teman in musholla al barokah, musholla al falah and musholla baitul muslimin. Research proves that the existence of musholla (x1) as well as the establishment of religious values (x2) has a 96.7% effect on children.